N '-5-Chloro-2-oxidobenzylidene-kappa O)-3-hydroxy-2-naphthohydrazidato-kappa N-2 ',O-2 diphenyltin(IV) - Lee, S.M.; Ng, S.W.; Ali, Hapipah Mohd; Lo, K.M. (International Union of Crystallography, 2009)
The Sn-IV atom in the title compound, [Sn(C6H5)(2)(C18H11ClN2O3)], is O,N,O'-chelated by the deprotonated Schiff base ligand and further bonded by two phenyl rings in a distorted cis-C2SnNO2 trigonal-bipyramidal geometry [C-Sn-C = 125.7 (2)degrees]. The two phenyl rings are oriented at a dihedral angle of 55.2 (3)degrees. Intramolecular O-H center dot center dot center dot N hydrogen bonding is present in the crystal structure.